2021
DOI: 10.1136/bmjopen-2020-042669
|View full text |Cite
|
Sign up to set email alerts
|

Association between objectively measured body composition, sleep parameters and physical activity in preschool children: a cross-sectional study

Abstract: ObjectiveAssociations between self-reported sleep duration and obesity indices in children are well recognised; however, there are no studies on associations between objectively measured other sleep parameters and physical activity with body composition in preschoolers. Therefore, the aim of this study was to determine the associations between sleep parameters and moderate-to-vigorous physical activity (MVPA) with body composition indices in preschoolers using objective measures.DesignA cross-sectional study.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…A positive correlation between shorter sleep duration and early childhood obesity was reported 48,49 53,54 . In a study conducted in China, Zong et al 45 found that daily watching TV ≥2 hours increases the risk of obesity by 2.154 times.…”
Section: Discussionmentioning
confidence: 91%
“…A positive correlation between shorter sleep duration and early childhood obesity was reported 48,49 53,54 . In a study conducted in China, Zong et al 45 found that daily watching TV ≥2 hours increases the risk of obesity by 2.154 times.…”
Section: Discussionmentioning
confidence: 91%
“…Though obesity is a multifactorial etiological condition (Park et al, 2019), that involves social, cultural, environmental and behavioral factors (Park et al, 2019), movement behaviors account for an important portion. Previous studies carried out with preschoolers showed that short sleep duration is a strong predictor of increased BMI (Carson et al, 2017;Ji et al, 2018;de Souza et al, 2021;Wyszy nska et al, 2021) due to the associated increase in cortisol secretion (Eythorsdottir et al, 2020;Fernandezmendoza et al, 2014;Marceau et al, 2019;Saridjan et al, 2017). Moreover, leptin and ghrelin dysregulation cause hunger and eating desire (Kroll et al, 2020), and a long awake period has been associated to an increased caloric intake (Poggiogalle et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, prior studies using a linear approach captured evidence on the association between sleep and BMI (Carson et al, 2017; Ji et al, 2018; de Souza et al, 2021; Wyszyńska et al, 2021). Nonetheless, exploring a multifactorial condition requires a multifactorial approach, as different determinants interact simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Сон менее 12 ч у младенцев является фактором риска избыточного веса и ожирения в дошкольном возрасте [35]. Продолжительность сна обратно пропорциональна ИМТ и процентному содержанию жира в организме [36]. Короткий сон в возрасте 10-13 лет увеличивал вероятность развития ожирения или избыточного веса в 1,6 раза в возрасте 16-19 лет [37].…”
Section: дошкольный и школьный возрастunclassified